2003
DOI: 10.1115/1.2006667
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Shroud Leakage Flow and Main Flow in a Three-Stage LP Turbine

Abstract: Endwall losses significantly contribute to the overall losses in modern turbomachinery, especially when aerodynamic airfoil load and pressure ratios are increased. In turbines with shrouded airfoils a large portion of these losses are generated by the leakage flow across the shroud clearance. Generally the related losses can be grouped into losses of the leakage flow itself and losses caused by the interaction with the main flow in subsequent airfoil rows. In order to reduce the impact of the leakage flow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…4-6 all made more detailed study of rim seal leakage flows in the compressor environment and found that the tangential velocity was a key parameter in the interaction of purge flow and endwall flow. Hunter and Manwaring, 7 Gier et al, 8 and Bohn et al, 9 focused their works on turbines. Mclean et al, 10,11 tested the radial, impingement and root injection cooling configurations.…”
Section: Introductionmentioning
confidence: 98%
“…4-6 all made more detailed study of rim seal leakage flows in the compressor environment and found that the tangential velocity was a key parameter in the interaction of purge flow and endwall flow. Hunter and Manwaring, 7 Gier et al, 8 and Bohn et al, 9 focused their works on turbines. Mclean et al, 10,11 tested the radial, impingement and root injection cooling configurations.…”
Section: Introductionmentioning
confidence: 98%
“…Abo El Ella, et al [4] also found that losses and flow overturning increased for an endwall with an upstream cavity relative to a smooth wall due to a separation in the cavity that strengthened the passage vortex. A loss breakdown scheme proposed by Gier, et al [5] suggested that steps between turbine components were responsible for 20% of the loss increase between a smooth-flowpath model and a more realistic model with leakage interfaces.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The work focused on the shroud leakage flows has demonstrated that the geometry of exit shroud cavity plays a crucial role in their interaction with the mainstream (e.g., Pfau et al [8] and Gier et al [9]). Schlienger et al [10] compared a rectangular cavity configuration with sharp edge corners and the one modified by placing inserts to allow a shallower injection angle.…”
Section: Introductionmentioning
confidence: 98%